2009
DOI: 10.1542/peds.2009-0160
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Respiratory Patterns in Healthy Term Infants Placed in Car Safety Seats and Beds

Abstract: In healthy term newborns, significant desaturations were observed in both car beds and car seats as compared with hospital cribs. This study was limited by lack of documentation of sleep stage. Therefore, these safety devices should only be used for protection during travel and not as replacements for cribs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
3
16
0
1
Order By: Relevance
“…Kornhauser and colleagues, for example, have elegantly shown that term infants have many more desaturations in a car seat than while resting in a crib (mean 17 vs 6 per hour), with significantly lower mean and minimum oxygen saturations. 6 The current study confirms a similar rate of moderate desaturations during sleep. Car seats are essential for the safe transportation of infants.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Kornhauser and colleagues, for example, have elegantly shown that term infants have many more desaturations in a car seat than while resting in a crib (mean 17 vs 6 per hour), with significantly lower mean and minimum oxygen saturations. 6 The current study confirms a similar rate of moderate desaturations during sleep. Car seats are essential for the safe transportation of infants.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, infants sleeping in the car seat with the insert had fewer obstructive apneic events, supporting the hypothesis that the insert can help reduce obstruction of the upper airway. 9,10,13 Consistent with previous studies, 3,[6][7][8][9] episodes of transient mild to moderate desaturation were common in otherwise healthy full-term infants restrained in car safety seats. Kornhauser and colleagues, for example, have elegantly shown that term infants have many more desaturations in a car seat than while resting in a crib (mean 17 vs 6 per hour), with significantly lower mean and minimum oxygen saturations.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations